BOLIVARIAN WAY: where does it come from, where is it going - Seabra, Raphael Lana (2013)
The aim of this paper is to present theoretical keys that could contribute to the analysis of the Venezuelan political, social and economic process in recent years, and the understanding of a possible "Bolivarian way" that has been taking form in its shortcomings and possibilities. The text comes to analytically separate Bolivarism of chavismo, in order to consider the possibilities of continuity of the revolutionary process, especially after the physical disappearance of Hugo Chavez. This analytical separation enables you to view subordinated groups and the specific nature of the consensus/conflict within the Bolivarian Revolution's ranks. Furthermore, it enables to raise some questions concerning democracy, socialism and profiteering in the possible directions of the Bolivarian way.